KEBIJAKAN PERPAJAKAN DALAM INVESTASI - Ari Purwadi (Perspektif, 2002)
Formerly in new economic policy in the Orde Baru era. "Tax Holiday" and "Tax Allowance " is launched to en chance capital inflow to Indonesia to accelerate Indonesian Development. However, by the renewal of UU National Tax/1983, is then given based on tax power, so that will he no difference tax treatment between national and foreign investor.